High-temperature stable single carrier hole only device based on conjugated polymers. Issue 13 (13th July 2018) - Alam, Shahidul; Fischer, Peter; Kästner, Christian; Singh, Chetan R.; Schubert, Ulrich S.; Hoppe, Harald
Abstract: Abstract : Thin hole transport layers are important elements in organic semiconductor-based devices. Metal oxides are an encouraging material class for this purpose, as they may provide sufficient hole conduction in combination with excellent electron blocking properties. Both, long-term device stability, which may often be limited by the thermal stability of interfaces, and higher temperature processing steps, benefit strongly from the existence of thermally stable metal oxide interlayers. Provided that thermally stable electrodes can be fashioned, the stability of organic active layers—for example, in organic field effect transistors, light emitting diodes, or photovoltaic (OPV) devices can be investigated. Here, we apply this concept and report about the study of hole mobility (µh ) in single-carrier-hole-only devices in dependence of thermal annealing up to the above the actual melting temperature of regio-regular poly(3-hexylthiophene-2, 5-diyl) (P3HT).